Organisms isolated in induced sputum samples in acute exacerbation of severe and very severe chronic obstructive pulmonary disease - Shrestha, S K; Adhikari, S; Karki, M; Mohsin, U R; Khunjeli, R; Srivastava, B; Chaudhary, R; Bhatta, S (Journal of Chitwan Medical College, 2017)
Acute exacerbations pose a very high economic burden on Chronic Obstructive Pulmonary Disease (COPD) patients and are commonly infective in nature. Gram’s staining and bacterial cultures are baseline investigations for sputum examination for COPD. This study evaluated these techniques for characterization and identification of various organism involved in acute infective exacerbations of COPD. Sodium Chloride (3%) induced sputum samples from 122 severe and very severe COPD subjects presenting in acute exacerbation who had history of frequent exacerbations and frequent antibiotics use were evaluated. The sputum samples were evaluated by Gram’s staining and bacterial culture from January 2013 to March 2014. Induction technique was able to obtain adequate samples from 86 (70.48% of 122) subjects. Gram’s stain showed 30 samples of Gram positive cocci (34.88%), 23 samples (26.74%) of Gram Negative Cocci and 50 samples (58.13%) of Gram Negative Bacilli. Bacterial culture showed predominant growth of Gram negative organisms including Pseudomonas sp, Acinetobacter sp, Klebsiella pneumoniae and Citrobacter Freundii. Gram negative bacilli are the most common isolated pathogens responsible for the acute exacerbation in severe and very severe COPDs with history of frequent exacerbations and hospital visits.